APPLICATION OF TELEMEDICINE IN PALLIATIVE CARE FOR PATIENTS WITH ADVANCED ENDOCRINE DISEASES: BENEFITS, CHALLENGES, AND PRACTICE RECOMMENDATIONS - Milić, Marko Kimi; Sinanović, Šćepan; Prodović, Tanja; Mitrović, Aleksandar; Stevanović, Tamara; Subotić, Slobodan; Jestrović, Vladimir; Ralić, Branislav (Medical Gazzette, 2026)
Background: Telemedicine is becoming an increasingly important component of healthcare, particularly in palliative care, where it contributes to improving access, continuity, and personalization of services. For patients with advanced endocrine diseases, the need for continuous monitoring and support makes this technology especially relevant. Objective: The aim of this paper was to identify the key benefits and challenges of implementing telemedicine in palliative endocrine care and to develop practice-based recommendations. Methods: A systematic review of 24 publications published between 2015 and 2024 was conducted, focusing on telemedicine within the context of palliative or endocrine care. The findings related to effectiveness, acceptability, and implementation challenges were analyzed. Results: The most commonly identified benefits of telemedicine included improved access to healthcare services (83.3%), more effective symptom monitoring (72.2%), increased patient satisfaction (66.7%), and reduced need for hospitalization (55.6%). Key challenges included technical issues and limited access to technology (77.8%), insufficient staff training (61.1%), and ethical-legal concerns (50%). Recommendations include staff education, development of specialized platforms, and enhancement of the regulatory framework. Conclusion: Telemedicine holds significant potential to improve the quality of palliative care in endocrine patients. However, successful implementation requires a comprehensive approach involving technical infrastructure, staff training, and supportive healthcare policies.